Mathematics: An Analytical tool to Study Student Perception towards Digital Banking Services - Dr. Sunita Dhote (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper tries to measure the students perception and expectation towards digital banking services. Now a days with advancement of technology, the banks through their different digital banking services wants to acquire more and more customers, wherein todays students are present and potential customers too. The article extensively tries to study the students perception towards the digital banking services, which are ATMs, credit cards, debit cards, internet banking, mobile banking, electronic fund transfer (EFT), electronic clearing system and the list is endless. The research has studied through a structured question are of 215 students pursuing graduation and post-graduation in Nagpur City.